The illustrated encyclopedia of 20th century weapons and warfare Breslau/Centurion - Authors: Bernard Fitzsimons (Editor), John Batchelor (Illustrator) (New York Columbia House, 1978)
Intro, Coverage, Warships, Aircraft, Tanks and APCs, Small Arms, Missiles, Artillery
Keywords: Weapons -- 20th century; Military art and science -- 20th century